A rede heterogênea em casos de dupla remoções forçadas: um estudo de caso - Duarte, Cícero Renato Feitosa (2021)
This research focuses on removals of people due to urban interventions. The main objective is to describe the heterogeneous networks present in the issue of removal of people due to urban interventions in the region of M'boi Mirim, in the city of São Paulo/SP. For this, we anchor ourselves on the assumptions of the Actor-Network Theory, with emphasis on the heterogeneous networks that perform removals as a fractal object composed of materialities and sociabilities. We used as a case study the removals that occurred in the Guarapiranga building, in Jardim São Luís, a district that integrates the mentioned Subprefecture. The information was produced from four conversations in daily life and an interview with our main interlocutor, Dona Maria